DESIGN OF THE DATA TRANSMISSION BETWEEN THE EXERSICE SMART MINE WITH GROUND STATION USING LORA - Gesit Pratiknyo; M Sigit Purwanto; Erpan Sahiri; Muladiyono Muladiyono (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Wireless data communication system through communication radio is one of the important points of informationdelivery process in TNI AL, It relates to the process of delivering information on the field that is difficult to obtaincommunication network via internet. The use of portable and strong communications against jammedinterference and other adjacent frequency interference becomes a fundamental necessity. The use of the UHFfrequency communication system is one of the efficient communication, With the high frequency of positivelyresulting in the physical size of the antenna is increasingly smaller. The purpose of designing datacommunication system devices between exercise smart mine and the ground station using Lora. In planning thiscommunication system uses the Lora SX1278 module as a data transmitter (Tx) and receiver data device (Rx).On the transmitter side (Tx) Lora uses the Arduino Mega 2560 microcontroller as the core or brain system. Onthe side of the receiver (Rx) Lora uses Arduino Uno R3 as the process data unit received by the Lora receiver.The main function of Arduino Uno as an intermediary to be able to transfer data to a PC or laptop device as aground station monitoring through USB communication channels. From the design, testing, and discussion ofresearch results during the preparation and manufacture of this final task obtained the results as expected. Thatthe design of data communication systems using Lora can be obtained a maximum range of 200 meters withthe condition of building obstructed. The ability of the Lora SX1278 module to receive data and transmit datafrom the GPS, pressure sensors and acoustic sensors is well received by the ground station, based on the datatransmitted via the Lora SX1278 module transmitter.Keywords: Lora SX1278, Arduino Mega 2560, Arduino Uno R3